2021
DOI: 10.1186/s13068-021-02079-6
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping of a Brazilian bioethanol strain links the cell wall protein-encoding gene GAS1 to low pH tolerance in S. cerevisiae

Abstract: Background Saccharomyces cerevisiae is largely applied in many biotechnological processes, from traditional food and beverage industries to modern biofuel and biochemicals factories. During the fermentation process, yeast cells are usually challenged in different harsh conditions, which often impact productivity. Regarding bioethanol production, cell exposure to acidic environments is related to productivity loss on both first- and second-generation ethanol. In this scenario, indigenous strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 99 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…Interestingly, plasma membrane lipid composition, in particular concerning the content in ergosterol and complex sphingolipids, determines the proper raft association of Gas1 and sorting of the plasma membrane [74], ultimately influencing its activity. Interestingly, a recent QTL mapping to uncover the genetic basis that confers to the bioethanol industrial strain Pedra-2 (PE-2) tolerance during growth at low pH, identified a non-synonymous mutation (A631G) in GAS1, prevalent in wild-type isolates and absent in laboratory strains [75]. The chitin content, assessed by the quantification of calcofluor white fluorescence intensity, also increased during acetic-acid-induced latency, with a time-course pattern similar to the β-glucan profile.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, plasma membrane lipid composition, in particular concerning the content in ergosterol and complex sphingolipids, determines the proper raft association of Gas1 and sorting of the plasma membrane [74], ultimately influencing its activity. Interestingly, a recent QTL mapping to uncover the genetic basis that confers to the bioethanol industrial strain Pedra-2 (PE-2) tolerance during growth at low pH, identified a non-synonymous mutation (A631G) in GAS1, prevalent in wild-type isolates and absent in laboratory strains [75]. The chitin content, assessed by the quantification of calcofluor white fluorescence intensity, also increased during acetic-acid-induced latency, with a time-course pattern similar to the β-glucan profile.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the genes found to be upregulated at low pH are related to cell wall biogenesis, including FKS1 (β1,3-glucan synthase), GAS1 (β-1,3-glucanosyltransferase involved in cell wall remodeling-elongation of (1 → 3)-β- D -glucan chains and branching), CHS1 (chitin synthase), NCW2 (GPI-protein involved in chitin-glucan assembly), KRE6 (glucosyl hydrolase required for β1,6-glucan synthesis) and MNN9 (mannosyltransferase subunit involved in wall protein mannosylation) ( De Melo et al, 2010 ; De Lucena et al, 2012 ; Figure 3 ). Interestingly, using QTL mapping to uncover the genetic basis of a bioethanol industrial strain Pedra-2 (PE-2) tolerance, a prevalent non-synonymous mutation (A631G) in GAS1 was identified during growth at low pH induced by sulfuric acid exposure, reinforcing the idea of the relevant role of this GPI-protein in yeast tolerance in acidic environments ( Coradini et al, 2021 ). Together with the up-regulation of genes related with 1,3-β-glucan synthesis, elongation, and anchoring, low pH stress leads to increased cell wall resistance to compounds with β1,3-glucanase activity and to the establishment of more alkali-sensitive linkages between CWPs and the β1,3-glucan network ( Kapteyn et al, 2001 ; De Melo et al, 2010 ; De Lucena et al, 2012 , 2015 ; Lucena et al, 2020 ).…”
Section: Yeast Response and Tolerance To Industrially Relevant Stress...mentioning
confidence: 95%